The Hyperbolization of Amirandarejaniani in the Context of Medieval Thought - Lekiashvili, Tinatin (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
One of the key issues in medieval literature is the miracle and the miraculous event. Hagiographic works abound with examples of miracles accomplished through divine power, and these examples carry great significance. The sanctity of hagiographic characters, confirmed by the miracles they perform, appeared as true and real to the medieval reader as the hagiographic text itself, since the reader knew that every hagiographer operated according to the principle of truth-telling; thus, the possibility of anything being fabricated or invented was out of the question. Secular literature developed on the foundations of medieval religious writing. Korneli Kekelidze devotes an extensive study to this issue in „The Holy Knight“, noting that in the formation of secular literature, an important role was played by earlier religious writing, which dominated until the eleventh century. As already mentioned, many elements characteristic of medieval ecclesiastical writing are also encountered in secular works. The miracle, which in hagiographic monuments is strongly marked in both form and content, is less evident in secular writings. However, the medieval perception of the supernatural as real provided the basis for the author’s conception of the impossible heroic deed - the hyperbolic act - and for the reader’s acceptance of it. We may thus conclude that secular literature reflects a unified structure of medieval thought, specifically, a transformation of the miracle model typical of hagiographic literature, which is expressed primarily through the hyperbolization of heroic actions in secular works. This article examines „Amirandarejaniani“ by Mose Khoneli from this perspective. „Amirandarejaniani“ abounds in astonishing and fantastic stories, impossible feats, which to the modern reader appear fabulous and unreal, but to the medieval reader were entirely natural. Conditioned by tradition, the medieval reader perceived miracles in hagiographic texts as true and indisputable facts. Accordingly, the astonishing, hyperbolized heroics of secular literary monuments, arising from the soil of ecclesiastical writing, were not unfamiliar to the medieval audience. Indeed, they were perceived as equally true as the miracles of religious literature.